2015
DOI: 10.1136/bjophthalmol-2014-306335
|View full text |Cite
|
Sign up to set email alerts
|

Blepharoptosis surgery in patients with myasthenia gravis

Abstract: Over a third of patients in our series required repeat surgery, which would be expected when the initial aim was to under-correct this group. In contrast to previous commentaries, the amount of eyelid excursion was not the main factor used to guide the surgical approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…External levator advancement, frontalis slings and tarsomyectomy are the procedures performed. As the aim of surgery is not aesthetic, undercorrection of ptosis is normally practiced to avoid complications such as lagopthalmos and exposure keratopathy (Bradley, Bartley, Chapman, & Waller, 2001;Litwin et al, 2015). Litwin et al in their review of 23 patients underwent ptosis correction surgery showed 87% of ptosis were corrected after one procedure at the final follow up of 29 months (Litwin et al, 2015).…”
Section: Ijphcsmentioning
confidence: 99%
See 2 more Smart Citations
“…External levator advancement, frontalis slings and tarsomyectomy are the procedures performed. As the aim of surgery is not aesthetic, undercorrection of ptosis is normally practiced to avoid complications such as lagopthalmos and exposure keratopathy (Bradley, Bartley, Chapman, & Waller, 2001;Litwin et al, 2015). Litwin et al in their review of 23 patients underwent ptosis correction surgery showed 87% of ptosis were corrected after one procedure at the final follow up of 29 months (Litwin et al, 2015).…”
Section: Ijphcsmentioning
confidence: 99%
“…As the aim of surgery is not aesthetic, undercorrection of ptosis is normally practiced to avoid complications such as lagopthalmos and exposure keratopathy (Bradley, Bartley, Chapman, & Waller, 2001;Litwin et al, 2015). Litwin et al in their review of 23 patients underwent ptosis correction surgery showed 87% of ptosis were corrected after one procedure at the final follow up of 29 months (Litwin et al, 2015). Seventeen percent of the patients needed to undergo second procedure because the first operation was complicated with exposure keratopathy (Litwin et al, 2015).…”
Section: Ijphcsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Japanese series found that seven of eight patients who underwent lid‐elevation procedures for treatment‐resistant myasthenic ptosis, present for at least 2 years and with minimal circadian changes, were satisfied with the outcome . The Mayo clinic described nine patients who underwent surgery for treatment‐refractory ptosis after trying MG therapies for at least 12 months; half of their cases required additional procedures owing to undercorrection of ptosis, but this is preferable to overcorrection and secondary‐exposure keratitis …”
Section: Managing the Disability Of Op‐mgmentioning
confidence: 99%
“…Lesions of the III cranial pair and Horner's syndrome are of neurogenic origin. Myasthenia gravis, a motor plaque disorder, is classified as of myogenic origin 3 . Direct trauma to the eyes 4 , ophthalmologic surgeries in which retractors are used to injure or disengage the aponeurosis 5 , craniofacial surgeries, and those of involutional or senile origin 6 are of aponeurotic causes.…”
Section: Introductionmentioning
confidence: 99%